PENGENDALIAN GERAK MOBILE ROBOT BERBASIS BCI (BRAIN COMPUTER INTERFACE) - Adbizar Asmon Rizal; Sastra Kusuma Wijaya (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
Has long been known that neurons in the human brain produces electrical waves that can be measured, these waves obtained by the Emotiv EPOC + to get a signal Electroencephalography (EEG) of 14 pieces of electrodes distributed along the human scalp. Brain Computer Interface (BCI) is a system that allows the control hardware using human brain signals using Electroencephalography (EEG). Brain Computer Interface can be used to control a variety of microcontroller-based devices such as mobile robot control, a robot arm, and wheelchairs to help disabled people. In this study, we developed a system that allows humans to control the direction of motion of the mobile robot wave Electroencephalography (EEG). The system consists of an Emotiv EPOC + Neuroheadset, computers, and mobile robots. Cognitive Suite provided by Emotiv is responsible for generating the necessary control measures to make the mobile robot to perform three different orders: move forward, turn right, and turn left. The experimental results show that the mobile robot can be controlled in real-time based on physiological changes the subject. Keywords: Brain Computer Interface, Emotiv EPOC+, Mobile Robot, Microcontroller.